Edgar & Ellen : mad scientists. Season one, volume one [videorecording (DVD)] (Lions Gate Entertainment [distributor], 2008)
These twisted twins use their fiendishly funny skills to create chaos for the residents of Nod's Limbs, and no one is safe from their hilarious high jinks! When they try to out-prank each other, life really gets kooky! Includes: the first 13 episodes.